Duane-Radial Ray syndrome a SALL4-Related Disorder. Report of a case in Chile - Jonathan Huserman; Catherine Diaz (Global Journal of Rare Diseases - Peertechz Publications, 2020)
The Duane-Radial Ray syndrome or Okihiro syndrome belongs to the SALL4-Related Disorders, a phenotypic spectrum, that additionally includes, acrorenoocular syndrome and Holt-Oram syndrome, caused by the alteration of the same gene, which has significant relevance in the mesoderm, the limbs, and the heart development. These syndromes are characterized by thumb alteration, radial deviation of the forearm, Duane anomaly, and variable involvement of other organs such as kidney or heart. The prevalence is unknown. This is a case report of a Chilean patient with a pathogenic variant that confirms the Duane Radial Ray syndrome previously not described in the population.